2012
DOI: 10.1038/srep00266
|View full text |Cite
|
Sign up to set email alerts
|

Activated human CD4+ T cells express transporters for both cysteine and cystine

Abstract: Because naïve T cells are unable to import cystine due to the absence of cystine transporters, it has been suggested that T cell activation is dependent on cysteine generated by antigen presenting cells. The aim of this study was to determine at which phases during T cell activation exogenous cystine/cysteine is required and how T cells meet this requirement. We found that early activation of T cells is independent of exogenous cystine/cysteine, whereas T cell proliferation is strictly dependent of uptake of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 32 publications
(54 reference statements)
4
81
0
1
Order By: Relevance
“…In lymphocytes, cysteine has been identified as rate limiting for cell growth and proliferation with a series of studies demonstrating a role for cysteine in regulating the proliferation of T-cells [21][22][23][24][25][26]. Redox conditions determine the equilibrium between the levels of cysteine (free thiol form) and cystine (disulfide bonded form).…”
Section: Amino Acid Availability Affects T-cell Proliferation and Actmentioning
confidence: 99%
“…In lymphocytes, cysteine has been identified as rate limiting for cell growth and proliferation with a series of studies demonstrating a role for cysteine in regulating the proliferation of T-cells [21][22][23][24][25][26]. Redox conditions determine the equilibrium between the levels of cysteine (free thiol form) and cystine (disulfide bonded form).…”
Section: Amino Acid Availability Affects T-cell Proliferation and Actmentioning
confidence: 99%
“…The alanine serine and cysteine transporter system (ASCT2/ Slc1a5), which also transports glutamine, is another solute carrier whose expression increases after T cell activation (Levring et al, 2012). It was recently found that loss of ASCT2 decreased glutamine import and impaired OXPHOS and glucose metabolism in activated CD4 T cells (Nakaya et al, 2014).…”
Section: Substrate Utilization In Activated T Cellsmentioning
confidence: 99%
“…The GSH system is also necessary for efficient lymphocyte proliferation. Notably, cystine, the rate-limiting factor in GSH biosynthesis, is supplied to lymphocytes during their encounter with DCs (28,29) and, upon activation, is taken up from the medium through the cystine/glutamate antiporter x c - (30). GSH facilitates the proliferation of T lymphocytes (23) and is necessary for their G 1 /S transition (31).…”
Section: The Trx and Gsh Systems In Cancermentioning
confidence: 99%